Arthroscopic Single-Portal Subscapularis Tendon Repair - You, Jae S. (Arthrosc Tech, 2020)
Tears of the subscapularis tendon can be challenging to diagnose and treat. Because the subscapularis plays an important role in shoulder function, careful arthroscopic evaluation and treatment are necessary to restore function. Previous surgical techniques have ranged from full open repairs to complex arthroscopic procedures needing suture passer and/or retriever devices. We describe an arthroscopic surgical technique of subscapularis repair through a single anterior portal using only penetrating graspers. This approach can be used for partial upper-border subscapularis tears, as well as complete and retracted subscapularis tendon tears.